Mehr als nur Töne: Aspekte des Gestischen in neuer Musik und im Musiktheater - Meyer-Denkmann, Gertrud 1918-2014 (Saarbrücken Pfau, 2003)
Practising music requires body movement. Body movement is gesture. And gesture is giving meaning. It transfers the reproduction of the musical text into sound speech. In her study, Gertrud Meyer-Denkmann traces one-composed gestures: in contemporary music theatre, in new instrumental music, in current video installations and in present-day raves.
Keywords: Gesticulation; Theater history; Music theater; Music history; Musical analysis